2018
DOI: 10.2147/ott.s170739
|View full text |Cite
|
Sign up to set email alerts
|

MSI2 knockdown represses extrahepatic cholangiocarcinoma growth and invasion by inhibiting epithelial–mesenchymal transition

Abstract: PurposeTo investigate the expression and functional role of Musashi2 (MSI2), an RNA-binding protein, in extrahepatic cholangiocarcinoma (eCCA).Patients and methodsWe measured MSI2 expression in human specimens and cell lines using Western blot and quantitative real-time polymerase chain reaction, and we analyzed its association with clinicopathologic features in eCCA patients. Univariate and multivariate analyses were performed to identify risk factors correlated with overall survival and disease-free survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Tumor size and metastasis are 2 key parameters for grading tumor stage. As expected, our meta-analysis of 6 studies enrolling 668 patients [ 8 , 11 , 13 , 15 , 16 , 22 ] suggested that increased MSI2 expression closely correlated advanced tumor stage (OR = 2.32, 95% CI: 1.60–3.38, P < .0001, fixed effects model, Fig. 2 D).…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…Tumor size and metastasis are 2 key parameters for grading tumor stage. As expected, our meta-analysis of 6 studies enrolling 668 patients [ 8 , 11 , 13 , 15 , 16 , 22 ] suggested that increased MSI2 expression closely correlated advanced tumor stage (OR = 2.32, 95% CI: 1.60–3.38, P < .0001, fixed effects model, Fig. 2 D).…”
Section: Resultssupporting
confidence: 80%
“…Eight studies comprising 939 patients reported the link of MSI2 expression with tumor size. [8,9,11,13,15,16,21,22] The pooled result implied that higher MSI2 was marginally correlated with larger tumor size (OR = 1.58, 95% CI: 0.97–2.59, P = .07, random effects model, Fig. 2A).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…We first found MSI2 silencing inhibited EGF-induced EMT in 2 PC cells, including inhibiting EGF-induced EMT-like cell morphology, EGF-enhanced cell invasion and migration, and EGF-stimulated change of EMT epithelia and mesenchyme markers. Similarly, MSI2 silencing represses extrahepatic cholangiocarcinoma growth and invasion by inhibiting EMT [33]. MSI2 silencing impairs cell proliferation and EMT in esophageal squamous cell carcinoma [34].…”
Section: Discussionmentioning
confidence: 97%